Uncovering and defragmenting the role of the Toll pathway in the innate immune responses of cultured crustaceans against viral pathogens - Arturo Sánchez‐Paz; Adriana Muhlia‐Almazán (Reviews in Aquaculture, 2020)
Shrimp farming is considered the fastest growing aquaculture industry in the last decades, with an average growth in production of ~15% per year. Unfortunately, this industry has been affected by the emergence of viral diseases, and currently, there are no commercially available therapeutics against these pathogens. Therefore, a deeper understanding of the immune system components induced by viruses is imperative for the development of antiviral therapies in these species. It is well known that the Toll‐like receptor (TLR) signalling is involved in activating the innate immune responses in crustaceans. Although numerous research papers deal with the response of the individual components of this pathway involved in the antiviral response on different crustacean species, the information is highly fragmented. This review provides a detailed picture of the general structure and role of Spätzle, Toll receptors, MyD88, Tollip, Tube, Pelle, Pellino, Dorsal, Cactus and DIF, the elements constituting the Toll‐like receptor participating in the innate immune response against viral diseases in crustaceans. It summarizes the current knowledge progress about the influence of the Toll pathway components on the expression of antimicrobial peptides involved in the antiviral response of crustaceans. In addition, this review compares the structural and functional roles of the elements identified in crustaceans, with those of the popular model organism Drosophila . This systematic review may contribute to identify the existing gaps in the knowledge of the Toll pathway in crustaceans and help to carry out further studies that may be useful for the management of viral diseases.